Identifying the themes of medical tourism business in Iran: A systematic review - Nafiseh Karimi Badrabadi; Sogand Tourani; Asef Karimi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Nowadays, medical tourism reports impressive growth in terms of number of persons, income, and number of countries involved in cross-border flows. It refers to people traveling abroad (from home to a target country) to obtain medical treatment. The present study aimed to identify the themes and codes of the medical tourism business in Iran. MATERIALS AND METHODS: We searched international databases (such as PubMed, Scopus, Embase, and Web of Science) and Iranian bibliography thesaurus and repositories (namely, Scientific Information Database and Magiran) using keywords such as medical tourism, international medical travel, and medical tourism business in the English and Persian literature, published between January 2000 and December 2019, identified with no restriction on the type of the studies. The data were analyzed based on the content analysis method. RESULTS: Out of 1054 articles, 14 were finally selected. In the end, eight themes of the medical tourism business including competitive pricing, safety and security, information and communication technology, labor market and human resources, structure management, leading the way in medical tourism, infrastructure, and exchange with the international world were identified which on the whole contain 45 codes. Most of the articles were quantitative. Four of the themes (competitive price, labor market and human resources, structure management, and infrastructure) were most frequent and of the highest importance. CONCLUSION: The themes and codes identified in this study helps companies and individuals who want to work in the field of medical tourism. According to this study, all 8 themes and 45 codes are of high value, but still, some themes are of higher value than others and special attention should be paid to them.